VALIDATING AN INSTRUMENT TO MEASURE OPEN INNOVATION PRACTICES IN RESEARCH COMMERCIALIZATION - Marina Muhammad Razaki; Mohammad Ismail; Nur Izzati Mohamad Anuar (Jurnal Manajemen dan Kewirausahaan, 2023)
The Open Innovation Practice is getting well known as an initiative to help increase the rate of commercializing research output. Implementing open innovation practices within academia is essential in facilitating collaboration, fostering knowledge sharing, and facilitating technology transfer between academic institutions and industries. This pilot study aims to investigate and assess the validity and reliability of the instrument used to measure open innovation practices. Quantitative methodology was employed in this study, and data were gathered via a survey from 109 respondents. The respondents are among the lecturers at public universities in Malaysia that are actively involved in the commercialization of research output. The descriptive analysis shows that the respondents often practice open innovation in commercializing their research output. During the Exploratory Factor Analysis (EFA), the findings indicated that the Kaiser-Meyer-Olkin (KMO) value for the open innovation practice is 0.885, showing no severe problem of multicollinearity and Barlett's Test of Sphericity demonstrates a statistically significant result. No item is eliminated in this study. Meanwhile, the reliability test for nine instrument items in open innovation practice is accepted with Cronbach's Alpha of 0.916. To conclude, the discovery from this study indicates that the instrument acquires high validity and reliability and is well prepared to be tested for future stages.